Project-Based Learning to Improve Course Understanding Plant Physiology - Santi, Triana Kartika (Budapest International Research and Critics University, 2021)
Project based learning is an instructional approach which uses contextual problems and the students have to research required information to solve those problems. This study was intended to improve the students' achievement on Physiology of plants subjects in UNTAG 45 Banyuwangi. The research target was the students fulfilled the standard minimum 70% toward all indicators observed in this study. This classroom action research was carried out into three cycles in which each cycle consisted of four phases of activities, they were planning, implementation, observation and reflection. The result of reflection revealed that all indicators contributed to improvement of the students achievement, such as, (a) the comprehension aspect of report result was on cycle I (68.12%), cycle II (69.54%), and cycle III (74.04%), (b) the comprehension aspect of discussion result on Cycle I (69.20%), cycle II (69.43%), and cycle III (76.25%), (c) comprehension aspect of test on cycle I (57.60%), cycle II (65.53%), and cycle III (74.48%). In sum, project based learning could improve all comprehension aspects and achieve the research target on cycle III.